Kautsar, T. R. (2023). Kajian Literatur Terstruktur Terhadap Kebocoran Data Pribadi Dan Regulasi Perlindungan Data Pribadi. APJII. (2023). Survei APJII Pengguna Internet di Indonesia Tembus 215 Juta Orang. APJII. https://apjii.or.id/berita/d/survei-apjii- - Ni Kadek Sriyulianti; ardhya, si ngurah; setianto, muhamad jodi (Jurnal Ilmu Hukum Sui Generis, 2024)
This research aims to analyze and examine the role of the Food and Drug Supervisory Agency in dealing with the distribution of illegal cosmetics in Buleleng Regency. The type of research used in this research is empirical juridical and descriptive. The sample used was non-probability sampling in the form of purposive sampling. Data collection techniques were carried out by means of observation, interviews, literature study and documentation. Data processing and analysis was carried out qualitatively. Based on the research conducted, it can be seen that the role of the Drug and Food Control Center in Buleleng Regency in dealing with the distribution of illegal cosmetics has not been maximized due to a lack of human resources which causes the inspection and enforcement process to take a long time considering that Buleleng Regency is a large area. The obstacles experienced by the Food and Drug Monitoring Center in Buleleng Regency in dealing with the distribution of illegal cosmetics are that there is still a lot of fictitious information on online shops which makes it difficult for officers at the Food and Drug Control Center in Buleleng Regency to collect detailed and complete information, apart from the public's legal awareness. which is still low is also an obstacle because people tend to say they don't know that the products they sell are illegal.